2011
DOI: 10.1111/j.1540-5885.2011.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Product Quality and New Product Performance: The Role of Network Externalities and Switching Costs*

Abstract: Research about the critical drivers of new product success is perhaps one of the thorniest issues confronting academic research in the field. Among them, product quality is considered a crucial element to obtain a competitive advantage. However, empirical evidence suggests low returns on product quality investments in new products, and consequent manager claims for an explanation of whether quality investments are fruitful for the firm. Recently, a new research stream has suggested that the role of other compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 69 publications
(168 reference statements)
3
29
1
Order By: Relevance
“…Distributors are crucial as they make the product available to users (e.g., Perks & Moxey, 2011). Producers of complementaries, and even competitors, are potential sources of strategic collaboration that can fortify demand for a new product (e.g., Molina-Castillo, Munuera-Alemán, & Calantone, 2011;Snow, Fjeldstad, Lettl, & Miles, 2011). Public organizations and educational institutions can contribute to commercialization by, for example, envisioning the use of an innovation in society (e.g., Troshani & Hill, 2009).…”
Section: Insert Table 5 Herementioning
confidence: 99%
“…Distributors are crucial as they make the product available to users (e.g., Perks & Moxey, 2011). Producers of complementaries, and even competitors, are potential sources of strategic collaboration that can fortify demand for a new product (e.g., Molina-Castillo, Munuera-Alemán, & Calantone, 2011;Snow, Fjeldstad, Lettl, & Miles, 2011). Public organizations and educational institutions can contribute to commercialization by, for example, envisioning the use of an innovation in society (e.g., Troshani & Hill, 2009).…”
Section: Insert Table 5 Herementioning
confidence: 99%
“…First, network externalities have an impact on customer attitudes and behaviors. For example, network externalities will increase increase customers' perceived switching costs [1] and have an impact on customers' continuous intention [11], behavioral intention [12], payment intention [3] and loyalty [2]. Second, existing studies have shown that network externalities have an impact on the survival of pioneers [13] and the new products performance [3].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…A common finding from these studies is that network externalities positively related to performance. For example, direct network externalities have a positive impact on long-term new product performance, while indirect network externalities have a positive impact on short-term new product performance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Network externality not only influence to product attributes (Basu et al, 2003) and performance (Molina-Castillo et al, 2011), but also its impact on entrepreneurs success (Acs et al, 2016) and firms survival (Srinivasan et al, 2004). Pervious works more especially in marketing literature reveals that existence of network externality has potential to causes of fluctuations and variations in demand and makes changes the behaviors of customers (Hellofs and Jacobson, 1999), even it influence on the time of market entry decisions (Shankar and Bayus, 2003).…”
Section: Hypothesis Developmentmentioning
confidence: 99%